Accretion, feedback and galaxy bimodality: a comparison of the GalICS semi-analytic model and cosmological SPH simulations - Cattaneo, A; Blaizot, J; Weinberg, D; Colombi, S; Dave, R; Devriendt, J; Guiderdoni, B; Katz, N; Keres, D (2006)
We compare the galaxy population of an SPH simulation to those predicted by the GalICS semi-analytic model and a stripped down version without supernova and AGN feedback. The SPH simulation and the no-feedback GalICS model make similar predictions for the baryonic mass functions of galaxies and for the dependence of these mass functions on environment and redshift. The two methods also make similar predictions for the galaxy content of dark matter haloes as a function of halo mass and for the gas accretion history of galaxies. Both the SPH and no-feedback GalICS models predict a bimodal galaxy population at z=0. The "red'' sequence of gas poor, old galaxies is populated mainly by satellite systems while, contrary to observations, the central galaxies of massive haloes lie on the "blue'' star-forming sequence as a result of continuing hot gas accretion at late times. Furthermore, both models overpredict the observed baryonic mass function, especially at the high mass end. In the full GalICS model, supernova-driven outflows reduce the masses of low and intermediate mass galaxies by about a factor of two. AGN feedback suppresses gas cooling in large haloes, producing a sharp cut-off in the baryonic mass function and moving the central galaxies of these massive haloes to the red sequence. Our results imply that the observational failings of the SPH simulation and the no-feedback GalICS model are a consequence of missing input physics rather than computational inaccuracies, that truncating gas accretion by satellite galaxies automatically produces a bimodal galaxy distribution with a red sequence, but that explaining the red colours of the most massive galaxies requires a mechanism like AGN feedback that suppresses the accretion onto central galaxies in large haloes.